2011
DOI: 10.1007/s13197-011-0384-2
|View full text |Cite
|
Sign up to set email alerts
|

Pericarp browning and quality management of litchi fruit by antioxidants and salicylic acid during ambient storage

Abstract: Different antioxidants and salicylic acid were tested to overcome pericarp browning and to maintain the postharvest quality of the litchi fruits at ambient storage. It was found that 0.5% salicylic acid, 1% isoascorbic acid and 1% N-acetyl cysteine performed better over sulphur dioxide (SO2) fumigation for most of the parameters under study. Application of 0.5% salicylic acid found superior to reduce the pericarp browning, relative leakage rate, and decay percentage. It was effective in reduction of polyphenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 20 publications
4
44
0
6
Order By: Relevance
“…There was a relation between L* values and electrolyte leakage and MDA content, which reconfirms the conclusion that EBR has protective effects against membrane disintegration. PPO and POD activities PPO plays a pivotal role in the process of enzymatic browning in several horticultural products (Kumar et al 2011). It promotes enzymatic browning by catalyzing the oxidation of phenolic compounds in the presence of oxygen.…”
Section: Pulp Browningmentioning
confidence: 99%
“…There was a relation between L* values and electrolyte leakage and MDA content, which reconfirms the conclusion that EBR has protective effects against membrane disintegration. PPO and POD activities PPO plays a pivotal role in the process of enzymatic browning in several horticultural products (Kumar et al 2011). It promotes enzymatic browning by catalyzing the oxidation of phenolic compounds in the presence of oxygen.…”
Section: Pulp Browningmentioning
confidence: 99%
“…In peach fruit alleviation of CI was achieved at 1 mM but failed at 0.7 mM or lower SA concentrations and in pomegranate fruit SA treatments, especially at 2 mM concentration, were highly effective in reducing CI and electrolyte leakage in the husk of pomegranate. Kumar et al (2011) reported that the application of salicylic acid led to reduce the litchi fruit pericarp browning, relative leakage rate, and decay percentage. It was effective in reduction of polyphenol oxidase (PPO) activity and improvement of anthocyanin pigments of the fruit pericarp.…”
Section: Chilling Injury and Electrolyte Leakagementioning
confidence: 99%
“…Plant hormone is a kind of naturally produced small molecular residues, which has been proven to be closely associated with plant development and stress resistance (Wang et al, 2014). A recent study has shown that, the application of plant hormone salicylic acid could significantly delay the pericarp browning and quality degradation of ambiently stored litchi fruit (Kumar et al, 2013). However, until now, there has not been a reported preservative method designed to retain the fresh weight of postharvest lettuce via the alleviation of transpiration through specifically closing the stomata.…”
Section: Introductionmentioning
confidence: 99%